STRIVE PNG: using a partnership-based approach in implementation research to strengthen surveillance and health systems in Papua New Guinea - Rachael Farquhar; Annie Dori; Sarah MacCana; Nakapi Tefuarani; Evelyn Lavu; Alyssa Barry; Stephan Karl; Leo Makita; Leanne Robinson; Moses Laman (BMC, 2022)
Abstract Successful implementation research requires effective and equitable relationships between policy-makers, researchers and implementers to effect evidence-based systems change. However, mainstream research grant models between Global North and Global South institutions often (unintentionally) reinforce power imbalances between partners, which result in missed opportunities for knowledge and learning exchange between policy-makers, researchers and implementers. This case study, centred on the STRIVE PNG project, describes how a partnership-based approach has been used to establish, maintain and review effective and equitable relationships between 13 partner organizations (independent research institutes, government health agencies and public health laboratories) to strengthen surveillance and health systems in Papua New Guinea (PNG). We provide an overview of key terms (with supporting conceptual frameworks), describe selected partnership processes and tools used within the project, and share observations regarding early outcomes achieved through this approach.